Perancangan Arsitektur Sistem Informasi Inventory Management System dalam Mendukung Smart Economy Kabupaten Sukabumi - Jamaludin, Jamaludin (Program Studi Teknik Informatika Universitas Pamulang, 2024)
Improving family food security (TATAPAK) is the Sukabumi District Government's Quick Win program in the Smart City Movement of the Smart Economy pillar. The program aims to improve nutrition and reduce stunting. However, the TATAPAK program runs in a traditional way without the help of information technology, while the smart city concept is closely related to the use of ICT. One of the problems that arises is during post-harvest handling by recording plant and vegetable stocks that are still manual, causing recording errors, long recording times and human error. This research proposes the design of an inventory management system information system architecture to overcome recording problems so that vegetable stocks can be monitored in real time. This IMS information system architecture design also includes a review of the city anatomy in Sukabumi District, the application of the NASSCOM Smart City Framework and analyzes cyber threats or attacks, how to prevent and security technologies used based on the CIA Triad and AAA Security Operation.